KONTRIBUSI ORANG TUA TERHADAP KEMAMPUAN BACA TULIS AL-QUR’AN ANAK - Rizqina Elok Hidayati; Dian Caesarianingtyas; Annisa Rahmasari; Muhammad Sholikin (Academica: Journal of Multidisciplinary Studies, 2021)
The role of parents in accompanying children is needed, especially when they are at home. This study aims to determine how much a parent can play in the development of the skills of children who read and write al-q ur 's. These donations are in the form of helping children read and write the Koran at home on their own. The target of this research is two families in need 02/03 of the sukoharjo baki facility. The study employed qualitative field research methods. Selection of research subjects uses data-collection methods using interviews, observations, and documentaries. Based on research, keywords that: parents play an important role in raising children, children learn more quickly when parents often instill motivation, a short but effective time better than long but less effective, reading and writing the Quran will have a significant impact on the child's personality.Keywords: Children; Contribution; Parent; Read and Write Quran